Realisasi Kesantunan Berbahasa Dosen dan Mahasiswa Dalam Pembelajaran Bahasa Indonesia di IAIN Padangsidimpuan - Nur Baiya Harahap; Ummi Aisyah Siregar (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This study aims to describe the realization of politeness in the language of lecturers and students in learning Indonesian at IAIN Padangsidimpuan. This type of research is qualitative and quantitative research using descriptive methods. The data collection techniques in this study were (1) observation, (2) recording, and (3) recording. To ensure the validity of the data collected, three techniques were carried out consisting of (1) observation persistence, (2) triangulation, and (3) referential adequacy (Moleong, 2007: 329). The approach used in this study is a descriptive qualitative and quantitative approach, namely primary data obtained by direct observation of the teaching and learning process between Indonesian language lecturers and students in the classroom. The formulation of the problem that has been determined will be answered in this study by using the theory that is set as an analytical knife to process field data in this study, namely: the study of language politeness theory. Sources of data used in this study by collecting primary data and secondary data, the primary data of this study were obtained directly during the teaching and learning process. it is concluded that the realization of politeness in the language of lecturers and students in learning Indonesian is the form of verbal and nonverbal speech which is divided into declarative, imperative and interrogative forms of speech. The principle of politeness in language focuses on the category of wisdom maxims. The results of this study are grouped into the realization of politeness in the language of lecturers and students in learning Indonesian on students' learning motivation at IAIN Padangsidimpuan. Based on the results of data analysis, the ranking of types of speech acts used by Indonesian language lecturers at IAIN Padangsidimpuan in the teaching and learning process was obtained. In the declarative form of speech is 66.66% with 66.95% nonverbal occurrence, then the imperative speech form is 16.67% with 15.55 percent nonverbal occurrence, and the third order is interrogative speech form of 16.67% with 17 nonverbal occurrences, 5%. Keywords: realization, language politeness, Indonesian language learning.